Human membrane type-4 matrix metalloproteinase (MT4-MMP) is encoded by a novel major transcript: isolation of complementary DNA clones for human and mouse mt4-mmp transcripts. - Kajita, M; Kinoh, H; Ito, N; Takamura, A; Itoh, Y; Okada, A; Sato, H; Seiki, M (1999)
Five distinct membrane-type matrix metalloproteinases (MT-MMP) have been reported by cDNA cloning. However, the mt4-mmp gene product (MMP-17) has not been identified yet in spite of the cDNA isolation [Puente et al. (1996), Cancer Res. 56, 944-949]. In this study, we re-examined the transcripts for human mt4-mmp by 5' RACE and identified two types of transcripts. The minor one corresponded to the cDNA reported by Puente et al. and failed to express protein, and the other is the major transcript that has an extended open reading frame and expressed 67 and 71 kDa translation products. Thus, functional mt4-mmp has been identified for the first time.